TRENDS IN THE DEVELOPMENT OF OPEN GOVERNMENT DATA IN EUROPEAN COUNTRIES IN 2022-2024 - Mohylna, Kseniia; Koibichuk, Vitaliia; Khan, Bhola (Socio-economic relations in the digital society, 2025)
This article investigates the trends in the development of open government data in European countries between 2022 and 2024, based on the Open Data Maturity Report. The relevance of the study is driven by the growing role of open data in ensuring transparency in public administration and supporting digital transformation. The main objective of the study is to classify European countries according to the dynamics of open government data development and to identify key differences in digital maturity. The study applies the Time Series K-Means clustering method to normalized digital maturity indicators of countries for the period 2022–2024. As a result, three typical trajectories of open data development were identified: countries with an average starting point but dynamic growth; leading states with high and stable openness indicators; and countries with the lowest levels of digital openness and unstable progress. The analysis of average cluster indicators showed that the main differences between groups lie in the impact of open data on socio-economic processes and compliance with technical standards. At the same time, there is a trend toward narrowing the gap between countries in terms of political governance of open data. The study concludes that structural inequalities persist among European countries in the development of open data policies, while common vectors of digital transformation are being confirmed. The findings may be used for comparative analyses of digital policies, improvement of national open data strategies, and assessment of the effectiveness of digital reforms. Promising directions for further research include a deeper analysis of the impact of open data on public governance, economic development, and social trust, as well as interregional comparisons of openness policy implementation.